Problematika Manajemen Pendidikan Islam Ma'had al Munawwaroh Cikupa - Wartono (INTIFA: Journal of Education and Language, 2024)
Islamic educational institutions are known as the oldest educational institutions in Indonesia, however, in terms of quality and managerial aspects, Islamic educational institutions are still second. This cannot be separated from the many challenges and problems of poor management that exist in some Islamic educational institutions. This article aims to examine the problem of implementing management in Islamic educational institutions. The method used in this article is a literature study by reviewing several literatures related to the theme that the author will study. The results show that one of the management problems in Islamic education institutions is the lack of Islamic education managers in meeting the needs and expectations of stakeholders, then there are still authoritarian and centralized leadership practices that apply in some Islamic education institutions, the existence of a dichotomy in Islamic education institutions which causes the emergence of two groups of scientists, the lack of competent human resources, especially in managerial aspects and the strength of several Islamic educational institutions in maintaining their local wisdom values, so this also has an impact on the reluctance of Islamic education to innovate in line with current developments. ABSTRAK Lembaga pendidikan Islam dikenal sebagai lembaga pendidikan tertua di Indonesia, akan tetapi dalam aspek kualitas dan manajerialnya lembaga pendidikan Islam masih di nomor duakan. Hal ini tidak lepas dari banyaknya tantangan dan problematika kurang baiknya manajerial yang ada di sebagian lembaga pendidikan Islam. Artikel ini bertujuan untuk mengkaji problem penerapan manajemen di lembaga pendidikan Islam. Metode yang digunakan dalam artikel ini adalah studi literatur dengan mengkaji beberapa literatur-literatur yang berkaitan dengan tema yang akan dikaji penulis. Adapun hasilnya menunjukkan bahwa salah satu problem manajemen di lembaga pendidikan Islam adalah kurangnya para pengelola pendidikan Islam dalam memenuhi kebutuhan dan harapan stakeholder, kemudian masih adanya praktek kepemimpinan otoriter dan sentralistik yang berlaku di sebagian lembaga pendidikan Islam, adanya dikotomi dalam lembaga pendidikan Islam yang menyebabkan timbulnya dua pengelompokan ke ilmuan, masih minimnya SDM yang berkompenten terutama dalam aspek manajerialnya dan masih kuatnya beberapa lembaga pendidikan Islam dalam menjaga nilainilai kearifan lokalnya, sehingga hal itu juga berdampak kepada enggannya pendidikan Islam untuk berinovasi sesuai dengan perkembangan zaman.